2015
DOI: 10.1016/j.matpr.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Input on Stellite 6 Coatings on a Medium Carbon Steel Substrate by Laser Cladding

Abstract: . (2015). Effect of heat input on Stellite 6 coatings on a medium carbon steel substrate by laser cladding. Materials Today: Proceedings, 2 (4-5), 1747-1754. Effect of heat input on Stellite 6 coatings on a medium carbon steel substrate by laser cladding AbstractStellite 6 was deposited by laser cladding on a medium carbon steel substrate (MS) with energy inputs of 1. kW (MS 1) and 1.8. kW (MS 1.8). The chemical compositions and microstructures of these coatings were characterized by atomic absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…An increasing laser power induces an intensified melting of the substrate and causes more pronounced melt dynamics/ dilution and temperature rise (Ref 29,57). As a result, the surface tension of the weld pool decreases (Ref 31), and the wettability angle converges asymptotically: cos(a) fi 1, whereas the height decreases in parallel with a constant powder feeding rate (Ref 8).…”
Section: Bead Geometry and Dilutionmentioning
confidence: 99%
“…An increasing laser power induces an intensified melting of the substrate and causes more pronounced melt dynamics/ dilution and temperature rise (Ref 29,57). As a result, the surface tension of the weld pool decreases (Ref 31), and the wettability angle converges asymptotically: cos(a) fi 1, whereas the height decreases in parallel with a constant powder feeding rate (Ref 8).…”
Section: Bead Geometry and Dilutionmentioning
confidence: 99%
“…The sliding wear behaviour of Stellite 6 coated samples produced by laser cladding has been investigated and reported for six high strength alloy substrates in recent publications by the authors [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the satellite-6 cladding was better than the SS. Alain Kusmoko et al [16] did stellite-6 cladding on medium carbon steel using laser cladding and found fewer cracks on the specimens which were coated by lower heat input. C.R.C Lima et al [17] compared the corrosion and wear property of stellite-6 cladding by TIG and high-velocity oxygen fuel (HVOF) process and found HVOF was having better wear resistance and TIG had better corrosion and erosion results.…”
Section: Introductionmentioning
confidence: 99%